Molecular Characterization of Danau Selais Fish (Ompok hypophthalmus) and Kaporeh Selais Fish (Ompok eugeneiatus) from Riau Province of Indonesia using Mitochondrial 12S rRNA - Roza Elvyra; Rio Riduan; Dewi Indriyani Roslim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The floodplain river in Riau is inhabited by various types of vertebrate animals including fish from the genus Ompok. The rapid development of species in the Ompok genus can cause ambiguity in species identity due to inaccurate identification processes. This research aims to analyze the molecular characteristics of two types of selais fish, namely danau selais fish (O. hypophthalmus) and kaporeh selais fish (O. eugeneiatus) from Riau based on 12S rRNA sequences. Methods included sampling of fishes from the Kampar, Tapung and Indragiri Rivers, the total DNA isolation, PCR, electrophoresis, sequencing and data analysis. In this study, the 12S rRNA DNA sequence of the selais fish studied was 939 bp in size. The sequences consisted of 803 bp of conserved sites (86.15%), 127 bp of variable sites (13.52%), 53 bp of parsimony sites (5.64%) and 73 bp of singleton sites (18.57%), with the composition of Adenine 31.7 %, Cytosine 26.9%, Thymine 20.9% and Guanine 20.4%. The average genetic distance between the two species was ±0.034, with the lowest genetic distance identified in the species O. hypophthalmus and O. eugeneiatus from the Indragiri River with a value of ±0.032, while the farthest genetic distance was identified in the species O. eugeneiatus from the Kampar River and the species C. gariepinus (Out group) with a value of ±0.092. Transition substitution (19.50%) occurs more frequently than transversion (10.94%). Phylogenetic reconstruction showed that the two species can be separated into distinct groups based on 12S rRNA sequences.